Primaquine in glucose-6-phosphate dehydrogenase deficiency: an adaptive pharmacometric assessment of ascending dose regimens in healthy volunteers - Pukrittayakamee, S; Jittamala, P; Watson, JA; Hanboonkunupakarn, B; Leungsinsiri, P; Poovorawan, K; Chotivanich, K; Bancone, G; Chu, CS; Imwong, M; Day, NPJ; Taylor, WRJ; et al. (eLife Sciences Publications, 2024)
Background: Primaquine is an 8-aminoquinoline antimalarial. It is the only widely available treatment to prevent relapses of Plasmodium vivax malaria. The 8-aminoquinolines cause dose-dependent haemolysis in glucose-6-phosphate dehydrogenase deficiency (G6PDd). G6PDd is common in malaria endemic areas but testing is often not available. As a consequence primaquine is underused.